Data collection on health care and its implications for child and adolescent development (International Seven Journal of Health Research, 2024)
This work arose from the need detected during a visit to the Basic Health Unit in the São João neighborhood in the municipality of Votuporanga/SP. Based on the information extracted, proposals were made for health promotion actions at school with high school students, the themes of which exposed the need for data collection in the area in question, which led to the development of this project. The transition from childhood to adolescence is an extremely important stage that requires special care, fundamental to the acquisition of autonomy and independence, essential for biopsychosocial development. Considering all the aspects mentioned, the importance of effective care and the strengthening of a comprehensive support and care network, involving various agents in a multidisciplinary way, is emphasized. Food is one of the main factors responsible for healthy growth and development during the transformations experienced by the individual. Another important aspect that influences an individual's development is a suitable environment that allows them to grow and develop without psychological limitations that hinder their integration into society. In addition, puberty is a phenomenon that generates physical and behavioural changes, which indicates the transition between childhood and adolescence, and can become precocious with the influence of various factors such as genetics, psychology, sexualization and diet. Results: Three meetings were held on different themes: Healthy eating, personal hygiene and puberty, with 72 children on alternate days and with different fun activities. The proposed objectives were successfully achieved, as the students' adherence to and understanding of the topics were satisfactory.